Friendship Quality and Happiness Among Adolescents Living Away from Home: Insights into Social and Academic Adjustment - Bella Arini Haq; Fatma Azmi Andirini; Mohammad Erlangga; Alaya Putri Ananda (International Journal of Post Axial: Futuristic Teaching and Learning, 2026)
Happiness can provide motivation, enthusiasm, and encouragement for teenagers in carrying out various activities both at school and outside of school. One way to get happiness for teenagers is through support and assistance from their family environment including parents, siblings and other extended family. On the other hand, there are some teenagers who live far apart from their parents and family as experienced by teenagers who migrate. Teenagers who feel happy will spend their time socializing and are happy to have more casual friends or close friends. Friendly friendships will help the social and emotional development of adolescents. This study uses correlational quantitative research, to determine the relationship between friendship quality and happiness in overseas adolescents. The results of the simple regression analysis showed a correlation coefficient (rxy) = .582 at p = 0.000 (p <0.05). A significance value of 0.000 (p<0.05) indicates that there is a positive significant relationship between the quality of friendship and the happiness of overseas adolescents.